First record of scelidodon chiliense (LYDEKKER) (Phyllophaga, Scelidotheriinae) from the lujanian stage (Late Pleistocene Early Holocene) of Argentina - Miño Boilini, Ángel Ramón (2009)
The Scelidotheriinae constitutes a group of sloth with numerous problematics, mainly related to their origin and phylogenetic relationships. This subfamily is principally characterized by a narrow and elongated skull, a coincident modification of the dental series and having a medium size. It is reported the first record of Scelidodon chiliense (LYDEKKER) (Phyllophaga, Scelidodieriinae), exhumed from Lujanian sediments (Late Pleistocene - Early Holocene) belonging to the Uspara Formation of San Luis Province (Argentina). The fossil (MHIN-UNSL GEO V-199) consists of a sub-complete skull without teeth, except the right Ml. The specific assignation is mainly based on: sagittal and temporal crests with little development and parietal and squamosal bones separated by an horizontal suture. This reports broad the geographical distribution of the species, known so far only for northern Chile, Bolivia, Peru and Ecuador. Finally, it allows raising and discussing some hypothesis related to its presence into the current territory of Argentina.